Sepsis in Infants: Analysis of Bacterial Pathogens and their Antibiotic Susceptibility, A Study at Government Tertiary Care Hospital, Karachi - Masood Hassan Rao; Sadia Khan; Tooba Waseem; Sabah Naeem; Sadaf Sabir (Journal of the Dow University of Health Sciences, 2013)
Objective: To assess the frequency of causative bacterial pathogen of sepsis in infant, their antibiotic susceptibility and to determine resistance pattern in commonly used antibiotics. Place and Duration of Study: Central Lab Civil Hospital, Karachi, 6 months. Study Design: Retrospective Descriptive observational study. Patients and Method: All 1414 reports of blood samples send for culture/sensitivity of infants admitted in Civil Hospital Karachi during the study period were scrutinized for bacterial pathogen, their frequency, antibiotic susceptibility and resistance pattern. Result: Out of 1414 infants, 604 (42.7%) had positive blood culture. Gram positive bacteria were predominant (54.1%) than gram negative (45.9%). Male: female ratio was found to be approximately 1:0.9. Total 9 organisms were isolated, in which staphylococcus aureus predominates followed by Pseudomonas aeruginosa and Escherichia coli respectively. The overall sensitivity of the organism to Amikacin and Cefotaxime were 60.87%and 36.67% respectively which are currently in use as empirical therapy in pediatric ward of CHK. The organisms were most sensitive to Vancomycin (95.54%), Sparfloxacin (94.16%), Linezolid (93.56%), while mostly resistant to kanamycin (56.21%), cephalosporins (55.9%), Gentamycin (54.31%) and amoxicillin (51.11%).